(untitled) (Scientific journal of the Fergana State University, 2024)
This research focuses on the interpretation of epithet compounds in the language, which is one of the methodological tools. Epithetic compounds, which contain phrases combined with adjectives or nouns, are common in English, but the mechanisms of their interpretation are still the subject of scientific research. Through a comprehensive study of language structures and cognitive processes, this study aims to shed light on the confusion and complexities in the interpretation of epithet compounds. In order to analyze epithet compounds, samples of English literature of the 20th century are referred to in the research. The analysis of the examples found will help to gain a deeper understanding of how epithet compounds function in language and their implications for language theory and cognitive processing.